INTEGRATION OF ISLAMIC VALUES IN PSYCHOSOCIAL INTERVENTION TO IMPROVE CHILDREN'S POSITIVE EMOTIONS PEOPLE LIVING WITH CANCER - Hendri; Iqbal Bafadal (AL-TAZKIAH, 2025)
Children with cancer face not only physical pain but also psychological distress such as isolation, limited activities, sadness, fear, and hopelessness. Islam-based psychosocial intervention is considered an appropriate approach to reduce negative emotions and foster positive ones. This study aims to describe the impact of Islamic psychosocial intervention on children with cancer at the C-Four Aceh shelter. A qualitative descriptive method was employed, using observation and interviews with 20 participants (children, parents, the foundation's chairperson, and staff). The findings indicate an increase in positive emotions, including cheerfulness, enthusiasm, calmness, and improved social interaction. Parents and staff also reported that the activities were beneficial in reducing boredom during medical waiting times and in nurturing new hope. The integration of Islamic values ??through singing religious songs, drawing Islamic themes, and practising mindfulness with dhikr made the intervention not only psychologically effective but also spiritually meaningful. This study highlights the importance of community-based psychosocial support rooted in Islamic spirituality as a holistic effort to strengthen emotional recovery in children with cancer.